Diversity dynamics of aerobic anoxygenic phototrophic bacteria in a freshwater lake - Villena-Alemany, Cristian; Mujakić, Izabela; Porcal, Petr; Koblížek, Michal; Piwosz, Kasia (Environmental microbiology reports, 2023)
Aerobic anoxygenic photoheterotrophic (AAP) bacteria represent a functional group of prokaryotic organisms that harvests light energy using bacteriochlorophyll-containing photosynthetic reaction centers. They represent an active and rapidly growing component of freshwater bacterioplankton, with the highest numbers observed usually in summer. Species diversity of freshwater AAP bacteria has been studied before in lakes, but its seasonal dynamics remain unknown. In this report, we analysed temporal changes in the composition of the phototrophic community in an oligo-mesotrophic freshwater lake using amplicon sequencing of the pufM marker gene. The AAP community was dominated by phototrophic Gammaproteobacteria and Alphaproteobacteria, with smaller contribution of phototrophic Chloroflexota and Gemmatimonadota. Phototrophic Eremiobacteriota or members of Myxococcota were not detected. Interestingly, some AAP taxa, such as Limnohabitans, Rhodoferax, Rhodobacterales or Rhizobiales, were permanently present over the sampling period, while others, such as Sphingomonadales, Rhodospirillales or Caulobacterales appeared only transiently. The environmental factors that best explain the seasonal changes in AAP community were temperature, concentrations of oxygen and dissolved organic matter.
Keywords: Phototrophic Processes; Alphaproteobacteria; aerobní bakterie; Bacteria, Aerobic; fototrofní procesy; Gammaproteobacteria; jezera; Lakes